Standardized postnatal management of infants with congenital diaphragmatic hernia in Europe: the CDH EURO Consortium consensus - Reiss, Irwin; Schaible, Thomas; van den Hout, L.; Capolupo, I.; Allegaert, K.; van Heijst, A.; Gorett Silva, M.; Greenough, A.; Tibboel, D. (Neonatology, 2010)
Congenital diaphragmatic hernia (CDH) is associated with high mortality and morbidity. To date, there are no standardized protocols for the treatment of infants with this anomaly. However, protocols based on the literature and expert opinion might improve outcome. This paper is a consensus statement from the CDH EURO Consortium prepared with the aim of achieving standardized postnatal treatment in European countries. During a consensus meeting between high-volume centers with expertise in the treatment of CDH in Europe (CDH EURO Consortium), the most recent literature on CDH was discussed. Thereafter, 5 experts graded the studies according to the Scottish Intercollegiate Guidelines Network (SIGN) Criteria. Differences in opinion were discussed until full consensus was reached. The final consensus statement, therefore, represents the opinion of all consortium members. Multicenter randomized controlled trials on CDH are lacking. Use of a standardized protocol, however, may contribute to more valid comparisons of patient data in multicenter studies and identification of areas for further research.
Gesehen am 12.05.2023